2014
DOI: 10.3390/pathogens3030510
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the Human Microbiome as a Contributor to Inflammatory Bowel Disease

Abstract: The human microbiome consist of the composite genome of native flora that have evolved with humanity over millennia and which contains 150-fold more genes than the human genome. A “healthy” microbiome plays an important role in the maintenance of health and prevention of illness, inclusive of autoimmune disease such as inflammatory bowel disease (IBD). IBD is a prevalent spectrum of disorders, most notably defined by Crohn’s disease (CD) and ulcerative colitis (UC), which are associated with considerable suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 109 publications
(146 reference statements)
1
22
0
Order By: Relevance
“…Recent murine studies have identified that functional microbial pathway alterations can be induced by sub-therapeutic administration of antibiotics as well. This evidence supports the idea that antibiotic therapy in IBD may reverse or improve the existing dysbiosis [5] .…”
Section: Ibd-associated Microbiome Changes Relative To Antibody Therapysupporting
confidence: 83%
See 4 more Smart Citations
“…Recent murine studies have identified that functional microbial pathway alterations can be induced by sub-therapeutic administration of antibiotics as well. This evidence supports the idea that antibiotic therapy in IBD may reverse or improve the existing dysbiosis [5] .…”
Section: Ibd-associated Microbiome Changes Relative To Antibody Therapysupporting
confidence: 83%
“…A dominant characteristic of patients with IBD is intestinal dysbiosis, a reduction in the diversity of bacterial species overall and especially in the number of beneficial microbes, such as Firmicutes (e.g., Faecalibacterium prausnitzii and Roseburia ), and an increase in enteric pathogens, such as adherent invasive E. coli and other Enterobacteriaceae [5] . The shift in bacterial species highlights the metabolic transition of the microbiome ecosystem from facultative to obligate anaerobes.…”
Section: The Gut Microbiome and Ibdmentioning
confidence: 99%
See 3 more Smart Citations